2003
DOI: 10.1089/152308603764816596
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Oxidized Low-Density Lipoprotein on Differential Gene Expression in Primary Human Endothelial Cells

Abstract: Oxidative modification of low-density lipoprotein (LDL) plays an important role in the initiation and progression of atherosclerosis. It has been proposed that the biological action of oxidized LDL (ox-LDL) may be partially attributed to its effect on a shift of the pattern of gene expression in endothelial cells. To examine the transcriptional response to ox-LDL, we applied cDNA array technology to cultured primary human endothelial cells challenged with oxidized human LDL. A twofold or greater difference in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 51 publications
2
15
0
Order By: Relevance
“…Zern et al (43) recently found that dietary supplementation with grape powder containing quercetin in preand postmenopausal women significantly decreased oxidative stress as measured by F2-isoprostanes and also decreased the levels of plasma TNFa. As previously demonstrated, TNFa and other cytokines and growth factors are stimulated by reactive oxygen species and ox-LDL (44,45). Our finding that quercetin supplementation did not decrease the concentrations of the proinflammatory cytokine TNFa might be explained by a general lack of quercetin to reduce TNFa under the conditions prevailing in the present study or could be due to the lack of oxidative stress in our study subjects.…”
supporting
confidence: 63%
“…Zern et al (43) recently found that dietary supplementation with grape powder containing quercetin in preand postmenopausal women significantly decreased oxidative stress as measured by F2-isoprostanes and also decreased the levels of plasma TNFa. As previously demonstrated, TNFa and other cytokines and growth factors are stimulated by reactive oxygen species and ox-LDL (44,45). Our finding that quercetin supplementation did not decrease the concentrations of the proinflammatory cytokine TNFa might be explained by a general lack of quercetin to reduce TNFa under the conditions prevailing in the present study or could be due to the lack of oxidative stress in our study subjects.…”
supporting
confidence: 63%
“…The source of lipids or lipoproteins, concentrations, time of exposure and the origin of the endothelial cells vary substantially among the studies. In agreement with our results, all the studies in which oxLDL were used to stimulate the cells show an enrichment in cell communication and cholesterol metabolism processes [36][37][38][39]. In addition, the response to stress process was a common trait with the studies that used oxPAPC [40,41].…”
Section: Discussionsupporting
confidence: 91%
“…These growth factors are produced by a variety of cells and are mitogenic for fibroblasts, smooth muscle cells (SMCs), and numerous other cell types, mainly of mesenchymal origin. Microarray analysis of HUVECs revealed that PDGF-A as well as PDGF-Rα are highly induced by oxLDL after 6 h of treatment (Virgili et al 2003). We have shown PDGF-A expression is induced by oxLDL occurred at the level of transcription (M.E., L.M.K., unpublished data).…”
Section: Platelet-derived Growth Factormentioning
confidence: 63%
“…Recent microarray analysis of HUVEC treated by oxLDL for 6 h revealed that VEGF as well as VEGF 155 R (neuropilin-1) and VEGFR2 (Flk1) are induced in these cells. Thus, oxLDL may induce VEGF signaling by increasing both the ligand and its receptors (Virgili et al 2003).…”
Section: Vascular Endothelial Growth Factormentioning
confidence: 99%